Analisis Kelayakan Usaha pada Minichick untuk Meningkatkan Kualitas Kinerja - I Wayan Septiadi; Yobert Kornelius; Harnida Wahyuni Adda; Nur Riski Islianty (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2024)
The purpose of this writing is to analyze the business proposal submitted by the MBKM Entrepreneurship team, namely the Minichicken business. This research uses descriptive qualitative and quantitative case study methods. The results of this research include that the Minichicken business is feasible to run, this is supported by structured and clear marketing aspects and supported by positioning that is different from its competitors with a strategic location and competitive prices. On the other hand, in terms of production, it has been well prepared, starting from the production process, production targets to production capacity. Apart from that, it is supported by financial aspects that support the return of capital in just 2 months and a BEP of 87 units. Therefore, it can be concluded that the Minichicken business is worth running.